Seasonal and Altitude Dependence of Thermospheric Metastable Helium Densities Measured by Fluorescence Lidar - C. Geach; B. Kaifler (Geophysical Research Letters)
Abstract Airglow originating from metastable helium He(23S) at 1,083 nm has been used to study the upper thermosphere since its discovery in 1959, yielding insights into, for example, solar EUV intensities and thermospheric photoelectron densities. For over 6 decades, these measurements were made passively, relying on solar illumination of the He(23S) layer to produce a detectable signal, resulting in a column integration of the He(23S) layer. Recently, the first height‐resolved measurements of He(23S) density were made by fluorescence lidar, opening a new window for studying the upper thermosphere. We report on a series of 51 measurements by this instrument spanning an entire winter season and extending to an altitude of 1,000 km, revealing a broad He(23S) layer that peaks at higher altitudes than previously expected.